A comparative study of radiofrequency ablation in unipolar and bipolar fashion - Wang, Y G; Lu, Z Y; Zhao, H Y; Song, Y E; Li, R L (Journal of Tongji Medical University, 1995)
In this study we compared the effects of radiofrequency (RF) energy applied to the swine endocardium in a unipolar fashion and in a bipolar one with two different interelectrode distances (5 mm, 10 mm). RF energy (500 kHz) delivered to the swine endocardium was divided into eight categories: 100 J, 101-200 J, 201-300 J, 301-400 J, 401-500 J, 501-600 J, 601-1000 J, and > 1000 J. The results showed that when RF energy was applied in a bipolar fashion, the lesions involved the catheter/tissue interface and partly the interelectrode spacing, while in a unipolar fashion. They were found in the catheter/tissue interface only. At any energy level, there were no statistically significant differences in lesion depths among all the three fashions, and the lesion surface areas produced by the bipolar fashion (with 5 mm or 10 mm interelectrode spacing) were all greater than those by the unipolar fashion (P < 0.05). When the delivered energy was under 500 joules, a greater lesion surface area was found in 5 mm bipolar fashion than in 10mm bipolar fashion (P < 0.05), while energy exceeded 500 joules, the differences in the lesion surface areas were no longer significant between these two bipolar fashions.